Formación inicial de los espermatofóros en el testículo del cangrejoUca uruguayensis (Brachyura: Ocypodidae) - I. Cuartas, Elena (2007)
The functional anatomy of the male reproductive system of Uca uruguayensis from Mar Chiquita lagoon, (37°45’ S, 57°26’ W), Argentina, was known only from optical microscopy. The present study describes the participation of vas deferens regions in spermatophore formation. A detailed description of the functional morphology of the different regions of the testicular lobes was carried out using both light and scanning electron microscopy. Spermatophore formation begins at the base of the testicular lobe. In most brachyuran species, the spermatophore starts formation when spermatozoa move from the collecting ducts of the testis to the vas defer-ens. However, in U. uruguayensis observations suggest that the formation of the spermatophore walls occurred in the terminal region of the testis, and that the spermatophore was formed at the junction of the testis and the vas deferens.